Trends and prospects of pulses and implications for nutrition - Chand, Ramesh; Sharan, Shambhavi (The Indian Journal of Genetics and Plant Breeding, 2017)
The ratio of per capita availability of cereals and pulses haschanged from 1: 0.152 during 1961-1965 to 1: 0.108 during2011-2013. This implies that for every kg of cerealsconsumed in the country, the amount of pulses consumedhas reduced to 71 per cent during the last fifty years. Thedecline in status of pulses production has distorted thedietary balance, aggravating the already existing undernutrition and malnutrition. Through this paper we try toexplore the causes for the slow growth in the productionof pulses and its role in the Indian agrarian economy. Wealso try to understand whether the changes in dietarybalance have been voluntary or forced by availability. Lastly,we try to investigate whether pulses help in addressing theissues of under nutrition and malnutrition in the country,or should we be complacent with food security based onrice and wheat alone.